2022
DOI: 10.1039/d2ra00954d
|View full text |Cite
|
Sign up to set email alerts
|

Highly stretchable, self-healing and conductive silk fibroin-based double network gels via a sonication-induced and self-emulsifying green procedure

Abstract: Silk fibroin-based double network gels, which were synthesized by the free radical polymerization via sonication-induced and self-emulsifying green procedure, exhibited highly stretchable, good self-healing and satisfactory conductive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The hydrophobic part of the polymer chain forms dynamic HA with the surfactant micelles, which serves as the physical cross-linking center to further improve the mechanical properties of the hydrogel. [42,43] It can be seen from Figure 3g-i that after the introduction of micelles, the tensile strain of the hydrogel was significantly increased, and the fracture force value was increased to 98 kPa, and the corresponding toughness was also significantly improved. The experimental results showed that the introduction of micelles was conductive to the mechanical properties of the hydrogel.…”
Section: Mechanical Properties Characterizationmentioning
confidence: 99%
“…The hydrophobic part of the polymer chain forms dynamic HA with the surfactant micelles, which serves as the physical cross-linking center to further improve the mechanical properties of the hydrogel. [42,43] It can be seen from Figure 3g-i that after the introduction of micelles, the tensile strain of the hydrogel was significantly increased, and the fracture force value was increased to 98 kPa, and the corresponding toughness was also significantly improved. The experimental results showed that the introduction of micelles was conductive to the mechanical properties of the hydrogel.…”
Section: Mechanical Properties Characterizationmentioning
confidence: 99%
“…[41,42] However, silk fibroin protein-based hydrogels are weak owing to the simple network structure formed by physical or chemical cross-linking, so it is important to improve the mechanical properties of hydrogels to meet actual application requirements. [43] Meanwhile, after a particular treatment like organic solvents, the mechanical characteristics of the silk fibroin hydrogels were improved, which however reduced the biocompatibility to some extent. [44] Many researchers attempted to fabricate silk fibroin MNs for drug delivery systems, but they are also unsuitable for long-term drug release due to poor mechanical properties and dissolvable ability resulting in burst drug release.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that SF prevents the coalescence of hydrophobic droplets in aqueous solutions and facilitates the formation of a stable oil-in-water emulsion. Wen et al used SF as a self-emulsifier to form an oil-in-water (o/w) emulsion by emulsifying 1-butanol in an aqueous SF solution without the need for any other surface-active agent . Emulsifying performance of SF in combination with a cosurfactant was also used to prepare a double-network hydrogel consisting of a physically cross-linked SF hydrogel and hydrophobically modified polyacrylamide as the first and second networks, respectively …”
Section: Introductionmentioning
confidence: 99%
“…25 Emulsifying performance of SF in combination with a cosurfactant was also used to prepare a double-network hydrogel consisting of a physically cross-linked SF hydrogel and hydrophobically modified polyacrylamide as the first and second networks, respectively. 29 Herein, we present a versatile strategy to prepare OHGs consisting of an SF hydrogel as the continuous phase and microinclusions based on poly(n-octadecyl acrylate) (PC18A), which is a semicrystalline polymer with a melting temperature of around 50 °C (Scheme 1). Recent works from our group show that the hydrogels and polymer blends based on PC18A exhibit superior properties including switchable mechanics and viscoelasticity, shape-memory, and self-healing functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation